Potential resources through the suitability and tourism carrying capacity of Kurenai Beach, Bone Bolango Regency - Sri Nuryatin Hamzah; Sri Fitriani Monoarfa; Veggy Arman (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
The lack of information regarding the existence of potential natural resources supporting tourism activities and the suitability and capability of resources to support the implementation of good tourism activities can be a factor that hinders the sustainability of tourism in Kurenai Beach. Beach tourism activities can make a positive contribution to economic growth and the level of community welfare. On the other side, these activities also negatively impact the sustainability of coastal resources. For this reason, it is necessary to limit the tourists according to the carrying capacity of Kurenai Beach. This research gave the initial information to support the sustainability and management of Kurenai Beach tourism, Bone Bolango Regency. This research aims to determine potential resources through regional suitability and carrying capacity. Further, it is expected that the result of this study can be used as a recommendation in preparing a tourism development policy plan for Kurenai Beach, Bone Bolango Regency. The research was conducted from March to August 2023 in Tomini Bay waters, Kurenai Beach. This is a survey and interview research. The types of data used in this research were primary and secondary. The analysis used in this research was suitability analysis and carrying capacity analysis to determine the resource potential of Kurenai Beach. The research results showed that the suitability of Kurenai Beach tourism in the beach recreation category was divided into 3 (three) suitability categories, namely very suitable (S1), suitable (S2), and not suitable (S3). The carrying capacity of the Kurenai Beach tourist area could accommodate around 33,840 people/month. Kurenai Beach has some potential resources that are very suitable for beach tourism, amounting to 15,379 m2 and the total visitors of Kurenai Beach has not exceeded the carrying capacity of the Kurenai Beach tourist area so optimizing its use and management is highly possible.Keywords:Natural resourcesSustainable tourismTomini BayBotubarani Village